1985
DOI: 10.1111/j.1600-0447.1985.tb02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased production of interferon alpha and interferon gamma in leucocyte cultures of schizophrenic patients

Abstract: In a first approach to measure the activity of the interferon system in schizophrenic patients, leucocyte cultures of schizophrenic patients and normal control individuals were set up using a whole blood assay. In this system both lymphoproliferation and the induction of interferon was tested. The lymphoproliferation (LP) test was performed with one bacterial recall antigen (PPD) and four different mitogens (phytohemagglutinin (PHA), concanavalin A (Con A), pokeweed mitogen (PWM) and a novel mitogen derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 7 publications
1
20
1
Order By: Relevance
“…Therefore, results showing decreased levels of IL-2 and IFN-Á in whole blood assays of schizophrenic patients under neuroleptic treatment cannot be attributed to influences of these drugs alone. Our data are supported by reports from other groups obtained in in vivo studies [4,8,20] and by a recent study in which the decreased IFN-Á levels and the significant correlation between IL-2 and IFN-Á in patients suffering from schizophrenia could be confirmed [16]. At the beginning of this study, patients were drug-naive or had not received any drug treatment for at least 6 months.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, results showing decreased levels of IL-2 and IFN-Á in whole blood assays of schizophrenic patients under neuroleptic treatment cannot be attributed to influences of these drugs alone. Our data are supported by reports from other groups obtained in in vivo studies [4,8,20] and by a recent study in which the decreased IFN-Á levels and the significant correlation between IL-2 and IFN-Á in patients suffering from schizophrenia could be confirmed [16]. At the beginning of this study, patients were drug-naive or had not received any drug treatment for at least 6 months.…”
Section: Discussionsupporting
confidence: 79%
“…Serum levels of IFN-Á do not seem to be elevated [23,32,33] although higher levels were reported by Preble and Torrey [34]. A tendency towards decreased production after stimulation has been reported [19,35,36]. In a group of psychotic patients which included schizophrenics and depressed patients, Inglot et al [37] showed a decreased production of IFN-Á.…”
Section: Introductionmentioning
confidence: 87%
“…In this study, no significant correlations between neuroleptic dosages and cytokines could be obtained. In one early study, Moises et al 27 did not find an in vitro effect of haloperidol, on either the proliferation of lymphocytes or on IFN-␥ production. In two clinical studies lymphocyte subpopulations were not influenced by neuroleptic treatment.…”
Section: Production Of: Il-2 (T1) Il-2 (T2) Il-2 (T3) Ifn-␥ (T1) Ifn-mentioning
confidence: 99%
“…Whilst there is some evidence that the mean serum levels of IFN-␥ in schizophrenics (except in one report) 20 resemble those of normal controls, [21][22][23] the production of IFN-␥ after mitogenic stimulation was only mildly and on the whole not significantly decreased in schizophrenia, 14,[24][25][26] although one study did find a significant decrease. 27 The lack of coherence in these results can be explained by the fact that studies varied considerably with respect to the use of bioassays, cell preparation techniques, and also recruitment of patients. Although in some studies cells were separated from the sera and subsequently stimulated by mitogens, our group used a whole blood assay 28 whereby the lymphocytes were incultured with as little deviation as possible from their physiological milieu, ie cell populations were present in their natural frequency and distribution.…”
Section: Introductionmentioning
confidence: 99%